Faktor-Faktor Yang Mempengaruhi Minat Masyarakat Dalam Usaha Ternak Babi Di Desa Petak Bahandang - Seth Miko; Susan Daniel; Yesninopy Yesninopy (Jurnal Ilmiah Kanderang Tingang, 2021)
The development of livestock business must be adjusted to the regional potential, the availability of feed, and socio-cultural conditions to increase the level of sustainability of the company. Raising pigs is one of the community's livelihoods in meeting the needs of life and rising household income. This research was conducted in Petak Bahandang Village, Gunung Mas Regency, which has many pig farmers. This study aims to determine the factors that influence people's interest in raising pigs. This research is field research, with the research method used being a qualitative descriptive method. The research results are that several factors influence people's interest in raising pigs, namely environmental conditions, initial capital, feed availability, marketing, and price guarantees.